1990
DOI: 10.2113/gsecongeo.85.8.1808
|View full text |Cite
|
Sign up to set email alerts
|

40 Ar/ 39 Ar and U-Pb geochronology of the Goonumbla porphyry Cu-Au deposits, New South Wales, Australia

Abstract: The 4øAr/39Ar technique of K-Ar dating has been used to determine the age of hydrothermal sericite associated with mineralization in the Goonumbla porphyry copper-gold deposits, Lachlan fold belt, New South Wales, Australia. The 4øAr/a9Ar age spectra from Goonumbla hydrothermal sericite indicate that vein and groundmass (potassic and phyllic) alteration were broadly contemporaneous at 439.2 q-1.2 Ma (la). The 4øAr/a9Ar dates obtained from hydrothermal alkali feldspar are considerably younger than those from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
33
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 11 publications
6
33
1
Order By: Relevance
“…The ca 439 Ma age for magmatism and alteration near Cadia is similar to that recorded at Goonumbla, near Parkes in the Junee -Narromine Volcanic Belt, where other ages include a 438 + 3.6 Ma U -Pb SHRIMP zircon age for a monzodiorite (Perkins et al 1990) and 439.2 + 1.2 Ma (Perkins et al 1990) and 440 + 1.1 Ma (Perkins et al 1995) The coarsely porphyritic and equigranular holocrystalline intrusions dated by radiogenic isotope techniques in the Cadia -Neville -Carcoar region (Figure 4) have shoshonitic geochemical affinities. However, the intrusions dated by Perkins et al (1992) from the Junction Reefs -Burnt Yards -Mandurama region have high-K calc-alkaline affinities (P. Blevin pers.…”
supporting
confidence: 64%
“…The ca 439 Ma age for magmatism and alteration near Cadia is similar to that recorded at Goonumbla, near Parkes in the Junee -Narromine Volcanic Belt, where other ages include a 438 + 3.6 Ma U -Pb SHRIMP zircon age for a monzodiorite (Perkins et al 1990) and 439.2 + 1.2 Ma (Perkins et al 1990) and 440 + 1.1 Ma (Perkins et al 1995) The coarsely porphyritic and equigranular holocrystalline intrusions dated by radiogenic isotope techniques in the Cadia -Neville -Carcoar region (Figure 4) have shoshonitic geochemical affinities. However, the intrusions dated by Perkins et al (1992) from the Junction Reefs -Burnt Yards -Mandurama region have high-K calc-alkaline affinities (P. Blevin pers.…”
supporting
confidence: 64%
“…Hydrothermal sericite associated with mineralization yields an 40 Ar/ 39 Ar step-heating age of 439.2 ± 1.2 Ma (Perkins et al 1990a). Uranium-Pb dating by ion microprobe on magmatic zircons from diorites near the Goonumbla deposits yields an age of 438 ± 3.5 Ma (Perkins et al 1990b).…”
Section: Nature Of Epithermal Gold Mineralizationmentioning
confidence: 99%
“…Data from Richards (1990a) setting, formed from high salinity fluids (Heithersay et al 1990;Heithersay and Walshe 1995;Wilson et al 2003), and were coeval with high-K igneous rocks (e.g. Perkins et al 1990a). Many Cretaceous to Cenozoic epithermal (e.g.…”
Section: Synthesis Of Direct Genetic Associationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The more evolved trachyandesites and coeval dioritic, monzonitic and syenitic intrusions were associated with the final subaerial evolution of the volcano, which included a large caldera. However, biostratigraphic and radiogenic age determinations (Perkins et al 1990(Perkins et al , 1992Packham et al 1999; suggested that the two episodes of shoshonitic volcanism were separated by between 15 and 20 million years. In addition, evidence from recent mapping and drillcore logging suggests that the Forest Reefs Volcanics include the products of at least two intrabasinal shoshonitic volcanic centres intercalated with a volcaniclastic apron, and that deposition and volcanism were entirely submarine.…”
Section: Introductionmentioning
confidence: 99%